Features of stem cells at different stages of ontogenesis - Колот, Н. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
In the process of ontogenesis all organs and tissues of humans and mammals retain" precursors" of embryonic tissue as «minor inclusions» of stem cells. Stem cells are involved in maintaining cellular homeostasis at all stages of ontogenesis, which is based on constant self-renewal of cells. The presence of stem cells in the organism does not protect it from the irreversible stage of ontogenesis – aging. The question is what changes occur in the stem cells at aging and to what extent or age-related changes are due to their somatic environment. The data are discussed and analyzed which show changes in the properties of stem cells and in their environment in ontogenesis, also the article describes analysis of gerontological research involving stem cells.